2023
DOI: 10.1155/2023/6341011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exosomal lncRNA MALAT1/miR-370-3p/STAT3 Positive Feedback Loop on PI3K/Akt Pathway Mediating Cisplatin Resistance in Cervical Cancer Cells

Abstract: Background. Exosomes can encapsulate lncRNA to mediate intercellular communication in cancer progression. Our study devoted to research the effect that long noncoding RNA Metastasis-associated lung adenocarcinoma transcript 1 (lncRNA MALAT1) influence on cervical cancer (CC). Methods. MALAT1 and miR-370-3p levels in CC was assessed using qRT-PCR. CCK-8 assay and flow cytometry were devoted to confirm the influence on MALAT1 influencing the proliferation in cisplatin-resistant CC cells. Futher more, MALAT1, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition, there are numerous extra-cardiac disease processes that may be affected by such genetic manipulation, the effects of which are hard to account for. For example, miR-370 has also been shown to play a regulatory role in various cancers, including cervical, ovarian, lung, gastric, and hepatocellular, among many others [ 156 , 157 , 158 , 159 , 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are numerous extra-cardiac disease processes that may be affected by such genetic manipulation, the effects of which are hard to account for. For example, miR-370 has also been shown to play a regulatory role in various cancers, including cervical, ovarian, lung, gastric, and hepatocellular, among many others [ 156 , 157 , 158 , 159 , 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…While miR-370-3p was inhibited by lncRNA MALAT1, STAT3 could be re-expressed and further bind the promoter of lncRNA MALAT1, resulting in a positive feedback regulation. On the contrary, lncRNA MALAT1 promoted the chemoresistance of CC cells through STAT3/PI3K/AKT pathway 128 . Lnc LRRC75A-AS1 was highly expressed in exosomes derived from M2 macrophages, inducing proliferation, migration, invasion, EMT, tumor growth, and metastasis of CC cells through downregulating miR-429 and SIX1/STAT3/MMP-9 signaling 129 .…”
Section: Exosomes In CCmentioning
confidence: 95%
“…Li et al found that long-stranded ncRNA uroepithelial carcinoma-associated 1 was upregulated in tissues and serum exosomes of cisplatin-resistant patients and promoted proliferation and resist cisplatin-induced apoptosis through the miR-143/FOSL2 signaling pathway [165]. Similarly, in cervical cancer tissues, lncRNA metastasis-associated lung adenocarcinoma transcript 1 was abundantly expressed in cisplatin-resistant cells and exosomes and inhibited cisplatin-induced apoptosis by targeting miR-370-3p [166]. Given that miRNA and lncRNA interactions are involved in chemoresistance phenotypes, exploring the mechanisms of miRNAs and lncRNAs in chemoresistance may help in the design of cisplatin antitumor therapies to improve patient outcomes.…”
Section: Lncrnas and Circrnas Regulate Mirnas Levels Involved In Cisp...mentioning
confidence: 99%